The potential protective effects of melatonin and omega-3 on the male rat optic nerve exposed to 900 MHz electromagnetic radiation during the prenatal period - Tüfekci, Kıymet Kübra; Kaplan, Arife Ahsen; Kaya, Ayşenur; Alrafiah, Aziza; Altun, Gamze; Aktaş, Abit; Kaplan, Süleyman (Informa UK Limited, 2023)
Due to children and adolescents' widespread use of electronic devices, researchers have focused on pre-and early postnatal electromagnetic field (EMF) exposure. However, little is known about the effects of EMF exposure on the optic nerve. The aim of study was to investigate the changes occurring in the optic nerve and the protective effects of melatonin (mel) and omega 3 (ω-3) in rats.Thirty-five pregnant rats were divided into seven groups, Cont, Sham, EMF, EMF + melatonin (EMF + Mel), EMF + ω3, Mel, and ω3. The EMF groups were exposed to 900 megahertz (MHz) EMF daily for two hours during pregnancy. After the experiment, the right optic nerve of each offspring rat was removed and fixed in glutaraldehyde. Thin and semi-thin sections were taken for electron microscopic and stereological analyses. Myelinated axon numbers, myelin sheath thicknesses, and axonal areas were estimated using stereological methods.The groups had no significant differences regarding mean numbers of axons, mean axonal areas, or mean myelin sheath thicknesses (p > 0.05). Histological observations revealed impaired lamellae in the myelin sheath of most axons, and vacuolization was frequently observed between the myelin sheath and axon in the EMF-exposed group. The Mel and ω-3-treated EMF groups exhibited well-preserved myelinated nerve fibers and intact astrocytes and oligodendrocytes.At the ultrastructural level, Mel and ω3 exhibits a neuroprotective effect on the optic nerve exposed to prenatal EMF. The protective effects of these antioxidants on oligodendrocytes, which play an essential role in myelin formation in the central nervous system, now require detailed investigation.
Keywords: Male; Adolescent; Supplementation; Field; melatonin; Axon; Antioxidants; Mobile Phones; Electromagnetic Fields; Pregnancy; Electrohypersensitivity; Humans; Animals; Polyunsaturated Fatty-Acids; Child; A2e Accumulation; Melatonin; Docosahexaenoic Acid; Electromagnetic Radiation; Brain; Rats; nucleator; fractionator; Female; Cell; omega-3; Antioxidant; 3. Good health